Time Outdoors in Nature to Improve Staff Well-Being: Examining Changes in Behaviors and Motivations Among University Staff in the Use of Natural Outdoor Environments Since the Emergence of the COVID-19 Pandemic - Loebach, Janet; Rakow, Donald A.; Meredith, Genevieve; Shepley, Mardelle McCuskey (Frontiers in Psychology, 2022)
Background Work-related stress is of growing concern to employers because of its significant implications for employee dissatisfaction, reduced productivity, and lowered emotional and physical health. Job-related stress is particularly acute among staff members in higher education, negatively impacting the professional work and personal welfare of staff. During the COVID-19 pandemic, stress levels increased, due to work- and non-work-related factors. Work expectations and environments shifted, as did new non-work responsibilities, such as care of dependents. As a result, many people were forced to spend much more time at home. Given the anticipated levels of stress (higher) and the change in time spent at home (increased), we sought to explore if adults were spending more time outdoors, as compared to pre-pandemic times, and if so, for what purposes. We hypothesized that people would be spending more time outdoors in nature during the pandemic, and that they would be doing so to achieve some of the well-documented benefits including managing stress, and bolstering mental health and wellbeing. We further hypothesized that some staff would experience barriers to spending time outdoors in natural outdoor environments (NOEs), potentially limiting their ability to experience these beneficial effects. Materials and Methods This study surveyed 507 staff from a large United States university to examine the degree to which staff were spending time in natural outdoor environments (NOEs) during the pandemic (two time-points, compared to pre-pandemic), and whether and how nature-based routines changed as a result of its emergence. The study also examined whether staff were motivated to spend time in nature to improve their mental health and/or wellbeing. Results The majority of respondents reported spending more time in NOEs since COVID-19 emerged, particularly early in the pandemic. Respondents reported doing so for restorative purposes, including stress relief, improved mental health, and improved physical health. Relative accessibility of NOEs, both in terms of proximity and number of barriers to access, significantly impacted both time outdoors and the number of NOEs used. Access to safe, high-quality NOEs was not experienced equally across staff respondents; barriers to access tended to be higher among staff living with dependents or others in their household, and for staff who identify as non-White. Conclusion Spending time outdoors may have served as a protective factor for many university staff against some of the potentially detrimental effects of the pandemic, particularly reduced mental health and well-being. Universities can contribute to the ongoing well-being of their staff by supporting access to safe, high-quality NOEs on or adjacent to campus. This may also serve to reduce disparities in access to nature and experience of its benefits. Universities may also consider alternative work arrangements for staff to allow for more time for health and wellness self-care during the work day, including spending time outdoors in nature.